"A New Way of Governing": Heinrich Brüning, Rudolf Hilferding, and Cross-Party Cooperation during the Waning Years of the Weimar Republic, 1930–1932. Issue 3 (September 2020) - McSpadden, James
Abstract: This article examines the unexpected behind-the-scenes relationship between the conservative Catholic chancellor Heinrich Brüning and Marxist theorist Rudolf Hilferding. This relationship is the starting point to understand both the politics of toleration and the political and cultural ecosystem in which this friendship came about. The German Social Democratic Party's policy of tolerating Brüning's conservative minority cabinet was hotly contested and has been viewed skeptically by political historians ever since. This article analyzes the mechanics of toleration through Brüning and Hilferding's relationship and demonstrates how Hilferding became the indispensable intermediary between the German cabinet and the socialist party. Toleration was a replacement political process in a polarized climate. A behind-the-scenes informal coalition that included the socialists, as well as the conservative cabinet, muddled through governing and policymaking with backroom negotiations instead of parliamentary debate. Although it failed, toleration was a last-ditch political strategy trying to preserve the Weimar Republic.